Підходи до діагностики соціально-економічного потенціалу регіону як основи ефективної стратегії управління - Кузьминчук, Наталія Валеріївна; Куценко, Тетяна Миколаївна (Сумський державний університет, 2016)
У статті досліджено методи кількісного оцінювання й аналізу розвитку соціально-економічного потенціалу регіону (у розрізі регіональних ресурсів), в результаті чого встановлено, що до цього часу відсутні єдина система показників регіонального розвитку та загальні методи об’єднання цих показників в один інтегральний кількісний показник. Усе це створює проблеми при оцінюванні й управлінні розвитком регіону. На основі концепції соціально-економічного потенціалу регіону, пропонується оцінювання регіональних ресурсів проводити за такими блоками: людський потенціал, майновий потенціал, соціальний потенціал. Запропонована система показників для оцінювання регіональних ресурсів дозволить вирішити проблему відсутності єдності в оцінюванні виділених показників та надасть можливість визначити основний напрям удосконалення управління регіональним розвитком на основі одержаних результатів.

The aim of article is development and justification of the directions of an effective strategy of regional development based on quantitative evaluation and analysis of the socio-economic potential of the region. In the article the methods of quantitative evaluation and analysis of the socio-economic potential of the region (in terms of regional resources), resulting in a set that is still no unified system of regional development and general methods of combining these indicators into one integrated quantitative index. All this creates problems when assessing and managing the development of the region. Based on the concept of socio-economic potential of the region, proposed the evaluation of regional resources to carry out the following blocks: human resources, property potential social potential. Summarizing the analysis of views of scientists on the possible assessment of the level of socio-economic potential of the region, we note that despite the constant improvement of definitions and study the factors that influence its components (human resources, property potential social potential) scorecard is imperfect and methodical approach to determine the integral index of socio-economic potential – incomplete or representative. Given the common goal of social and economic development and the need to determine the direction of development of the region for the long term, the prospects for future research aimed at developing new approaches to the study of regional resources in terms of their ability to provide current and future needs of the population.
Keywords: регіональний розвиток; регіональні ресурси; рівень життя; якість життя; соціально-економічний потенціал регіону; регіони; управління регіональним розвитком; regional development; regional resources; quality of life; economic potential of region